answersLogoWhite

0


Best Answer

63 = (2x3)3 = 23 x 33

36 = 33+3 = 33 x 33

As 2 ≠ 3 then 23 ≠ 33

⇒ 63 = 23 x 33 ≠ 33 x 33 = 36

⇒ 63 ≠ 36

User Avatar

Wiki User

โˆ™ 2011-08-26 09:31:49
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.76
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
853 Reviews

Add your answer:

Earn +20 pts
Q: Why isn' t 6 to the third power equal to 3 to the sixth power?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked